2015
DOI: 10.4103/0973-029x.164534
|View full text |Cite
|
Sign up to set email alerts
|

An in vitrostudy of antifungal drug susceptibility of Candida species isolated from human immunodeficiency virus seropositive and human immunodeficiency virus seronegative individuals in Lucknow population Uttar Pradesh

Abstract: Background:Candidiasis is the most common opportunistic infection in human immunodeficiency virus (HIV) seropositive patients, starting from asymptomatic colonization to pathogenic forms and gradual colonization of non-albicans in patients with advanced immunosuppression leads to resistance for azole group of antifungal drugs with high rate of morbidity and mortality.Objectives:To isolate the Candida species and determine of antifungal drug susceptibility against fluconazole, itraconazole, nystatin, amphoteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…14 But, there were also research that showed that some species were resistant to nystatin, like in the study held by Dar et al in India (2015) stated that 61.1% subjects were sensitive, 36.1% intermediate, and 2,8% resistant to nystatin. 15 This could be caused by the changes in sterol composition in the Candida's cell membrane that could decrease the affinity of the this drug to the membrane itself. 7,16 TTO 5% exhibited the antifungal effect against Candida sp.…”
Section: Discussionmentioning
confidence: 99%
“…14 But, there were also research that showed that some species were resistant to nystatin, like in the study held by Dar et al in India (2015) stated that 61.1% subjects were sensitive, 36.1% intermediate, and 2,8% resistant to nystatin. 15 This could be caused by the changes in sterol composition in the Candida's cell membrane that could decrease the affinity of the this drug to the membrane itself. 7,16 TTO 5% exhibited the antifungal effect against Candida sp.…”
Section: Discussionmentioning
confidence: 99%
“…that are rarely found in immunocompetent patients were also found in HIVseropositive patients, namely Candida dubliniensis, Candida glabrata, and Candida guilermondii. 18 A meta-analysis study conducted in Sub-Saharan Africa in 2005 -2015 showed a prevalence of non-albicans Candida species as much as 33.5% dominated with Candida glabrata, Candida krusei, and Candida tropicalis. The high prevalence of Candida krusei and Candida glabrata in HIV-infected populations in Sub-Saharan Africa has become a public health concern because this species is associated with fluconazole resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In India, an in vitro study of antifungal drug susceptibility of Candida species from human immunodeficiency virus (HIV) positive and HIV negative patients with and without oropharyngeal candidiasis has recently been published [3]. Candida isolates from HIV negative It should be noted, however, that nystatin-resistant isolates of C. albicans have repeatedly been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation can be found for nystatin. However, in vitro susceptibility testing studies have shown a low percentage of Candida species isolated from HIV positive patients to be resistant to nystatin [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation